Analysis of the Correlation and Regression Analysis Studies from the Korean Journal of Women Health Nursing over the Past Three Years (2007~2009). - Eun-Joo Lee; Eun-Hee Lee; Jeung-Im Kim; Hee Sun Kang; Hyun Ei Oh; Eun Mi Jun; Suk-Hee Cheon (Korean Journal of Women Health Nursing, 2011)
Purpose: This study investigated the statistical methods and the results had reported correlation/regression analysis in the studies of Korean Journal of Women Health Nursing (KJWHN). Methods: We reviewed 45 studies using correlation/regression analysis for the suitability of the statistical methods and the research purposes, the criteria for analysis of figures, tables and charts had published in the KJWHN from vol 13 (1) in 2007 to vol 15 (4) in 2009. Results: Forty three studies were fitted to their statistical methodology and their research purposes. Eleven studies considered the minimum sample size. Fourteen regression studies used multiple regression and 12 studies used forward method for variable entry. Only one study among the 17 regression studies accomplished scatter plots and residuals examination. Sixteen studies in correlation studies and six studies in regression studies showed some errors in either the title, variables, category of figures, tables and charts. In the regression study, all reported R2 and â values except one. Conclusion: It was found that there were still statistical errors or articulation errors in the statistical analysis. All reviewers need to be reviewed more closely for detecting errors not only during reviewing process of the manuscript but also periodic publication for the quality of this academic journal.